2006
DOI: 10.1189/jlb.0806517
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying TGF-β1-induced expression of VEGF and Flk-1 in mouse macrophages and their implications for angiogenesis

Abstract: TGF-beta induces vascular endothelial growth factor (VEGF), a potent angiogenic factor, at the transcriptional and protein levels in mouse macrophages. VEGF secretion in response to TGF-beta1 is enhanced by hypoxia and by overexpression of Smad3/4 and hypoxia-inducible factor-1alpha/beta (HIF-1alpha/beta). To examine the transcriptional regulation of VEGF by TGF-beta1, we constructed mouse reporters driven by the VEGF promoter. Overexpression of HIF-1alpha/beta or Smad3/4 caused a slight increase of VEGF promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
104
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 62 publications
0
104
0
1
Order By: Relevance
“…In this context, we have demonstrated that Runx3 synergizes with Smad3/4 to induce Ig germ-line α transcription leading to IgA isotype switching (Park et al, 2003). In addition, HIF-1α cooperates with Smad3/4 to mediate TGFβ1-induced VEGF transcription in mouse macrophages (Jeon et al, 2007). The present data indicate that CREB could play this role in TGFβ1-inducible APRIL transcription.…”
Section: Discussionmentioning
confidence: 50%
“…In this context, we have demonstrated that Runx3 synergizes with Smad3/4 to induce Ig germ-line α transcription leading to IgA isotype switching (Park et al, 2003). In addition, HIF-1α cooperates with Smad3/4 to mediate TGFβ1-induced VEGF transcription in mouse macrophages (Jeon et al, 2007). The present data indicate that CREB could play this role in TGFβ1-inducible APRIL transcription.…”
Section: Discussionmentioning
confidence: 50%
“…Also, although CX3CL1 directly stimulates angiogenesis, the local microvasculature also depends on several other growth factors, including VEGF and TGF-␤, which are produced by macrophages in wounds (60 -64). TGF-␤ signaling is able to up-regulate VEGF expression in various cell types (65)(66)(67)(68). We also found significant decreases in VEGF gene expression at wound sites in CX3CR1 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that TGF-b1 function is mitogenically conversed in prostate carcinoma cells through the activation of the oncogenic Ras-MAPK signaling pathway (Park et al, 2000). TGF-b1 is involved in blood vessel formation and one of its oncogenic functions is to promote tumor angiogenesis, which is associated with its ability to induce VEGF expression (Benckert et al, 2003;Sugano et al, 2003;Jeon et al, 2007). A recent study demonstrated that TGF-b1 activates migration and invasion of intermediary basal epithelial cells of the prostate by induction of VEGF receptor type 3 and matrix metalloproteinase-2/9, indicating that TGF-b1 is involved in cell phenotype changes associated with transitions to a malignant behavior (Goodyear et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of VEGF and its receptors are increased in prostate cancer cells compared with normal prostate epithelial cells, and elevated VEGF is implicated in angiogenic and non-angiogenic events, which are associated with tumor progression, including early tumor spread (Jackson et al, 2002;Pallares et al, 2006). TGF-b1 has an important role in angiogenesis, and one of the tumor-promoting functions of TGF-b1 is associated with its ability to induce VEGF (Benckert et al, 2003;Sugano et al, 2003;Wang et al, 2004;Jeon et al, 2007). Recently, it was reported that TGF-b1 activates cell migration and invasion by coordinated induction of VEGF receptor type 3 and matrix metalloproteinase-2/9 in intermediary basal epithelial cells of the prostate, suggesting that TGF-b1 is involved in phenotype changes associated with transitions to a malignant behavior (Goodyear et al, 2009).…”
Section: Introductionmentioning
confidence: 99%